Kinetics of Thermal Decomposition of Polymethylmethacrylate in an Oxidizing Environment; Russian Journal of Physical Chemistry B; Vol. 18, iss. 4 - Salgansky E. A. Evgeny Aleksandrovich (2024, 2024)
Title screen